Parallel circuits control temperature preference in Drosophila during ageing. - Shih, H.W.; Wu, C.L.; Chang, S.W.; Liu, T.H.; Sih-Yu Lai, J.; Fu, T.F.; Fu, C.C.; Chiang, A.S. (Nature communications, 2015)
The detection of environmental temperature and regulation of body temperature are integral determinants of behaviour for all animals. These functions become less efficient in aged animals, particularly during exposure to cold environments, yet the cellular and molecular mechanisms are not well understood. Here, we identify an age-related change in the temperature preference of adult fruit flies that results from a shift in the relative contributions of two parallel mushroom body (MB) circuits-the ?'- and ?-systems. The ?'-circuit primarily controls cold avoidance through dopamine signalling in young flies, whereas the ?-circuit increasingly contributes to cold avoidance as adult flies age. Elevating dopamine levels in ?'-afferent neurons of aged flies restores cold sensitivity, suggesting that the alteration of cold avoidance behaviour with ageing is functionally reversible. These results provide a framework for investigating how molecules and individual neural circuits modulate homeostatic alterations during the course of senescence.